Pharmaceutical Development and Standardization Mamajjaka Ghanavati - Vyas, Dr. Manish (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Ethnomedicine is contributed to the evolution of different systems of medicine, namely, Ayurveda, Siddha, Unani, and Naturopathy including the modern medicine. Enicostemma littorale blume [E. littorale (Mamajjaka)] is one of the traditional medicines used mainly in Gujarat, Madhya Pradesh, and Rajasthan as a stomachic, tonic, carminative, and appetizer. It is generally prescribed in the form of pills (Ghanavati) for the treatment of Type 2 diabetes in Ayurveda. Recent studies based on the antidiabetic effect of E. littorale suggest its role to reduce blood glucose by increasing serum insulin level. However, standards of Mamajjaka Ghanavati are not available in the official monographs. Objective: The study was designed to develop standards for the preparation and evaluation of Mamajjaka Ghanavati. Results and Discussion: The formulation is complying with the all standards available for the pills in the Ayurvedic Pharmacopoeia of India including hardness, friability, disintegration, and weight variation. High-performance thin-layer chromatography study revealed the presence of many phytoconstituents in the formulation.